Comparative Analysis of Set-Back Field Jumps In Multi-Storey Building Structures Due To Earthquake Load - A. Didik Setyo Purwantoro; Alfina Maysyurah; Siti Julaeka; Muhammad Nur Fajar; Herlina Arifin (Universitas Islam Sultan Agung, 2023)
Set-back jumping plane out due to earthquake depends. The purpose of this study is to determine what percentage of set-back field jumps are safe in multi-storey building structures when given earthquake loads, evaluate the behavior of building structures when viewed based on displacement and drift ratio and evaluate the effect of the elevation height of the set-back field jumps on building safety.In this study, the building is modeled as high as 7 floors and 6 floors with elevation heights of 28 m and 24 m using the SAP 2000 program which is used to analyze earthquake forces with the variational response spectrum method. The modeling studied was 8 modeling, namely at a height of 7 floors (building structure with set-back out 50%, 30%, 20% and 10%) and at a height of 6 floors (building structure with set-back out 50%, 30%, 20% and 10%). Based on the results of the research that has been done, the percentage of safe set-back exit plane jumps in the 7-storey high-rise building structure is in the modeling with a 10% set-back exit because the displacement value is below the allowable limit. As for the 20% and 30% set-back modeling, the displacement value of the top floor exceeds the allowable limit value. However, if the number of floors in the set-back section is reduced by 1 floor (to 6 floors) the structure is safe for every percentage of modeling.